Oxidative post-translational modifications and their involvement in the pathogenesis of autoimmune diseases. - Ryan, B; Nissim, A; Winyard, P (Elsevier, 2014)
Tissue inflammation results in the production of numerous reactive oxygen, nitrogen and chlorine species, in addition to the products of lipid and sugar oxidation. Some of these products are capable of chemically modifying amino acids. This in turn results in changes to the structure and function of proteins. Increasing evidence demonstrates that such oxidative post-translational modifications result in the generation of neo-epitopes capable of eliciting both innate and adaptive immune responses. In this paper, we focus on how free radicals and related chemical species generated in inflammatory environments modulate the antigenicity of self-proteins, resulting in immune responses which involve the generation of autoantibodies against key autoantigens in autoimmune diseases. As examples, we will focus on Ro-60 and C1q in systemic lupus erythematosus, along with type-II collagen in rheumatoid arthritis. This review also covers some of the emerging literature which demonstrates that neo-epitopes generated by oxidation are conserved, as exemplified by the evolutionarily conserved pathogen-associated molecular patterns (PAMPs). We discuss how these observations relate to the pathogenesis of both human autoimmune diseases and inflammatory disease, such as atherosclerosis. The potential for these neo-epitopes and the immune responses against them to act as biomarkers or therapeutic targets is also discussed.